KEPADATAN DAN STRUKTUR POPULASI MONYET EKOR PANJANG (Macaca fascicularis) DI KAWASAN HUTAN KOTA TELUK AKAR BERGANTUNG KETAPANG KALIMANTAN BARAT - Jannah, Farida Nurul; Erianto, .; Dewantara, Iswan (Universitas Tanjungpura, 2019)
Long-tailed macaque (Macaca fascicularis) are one of the primates that are quite widespread in Indonesia, one of its in the area of Teluk Akar Bergantung city forest on Ketapang, West Kalimantan. This study aims to obtain data on the number of groups, number of individuals, population density, and structure of long-tailed macaque populations in the region using the line transects method and concentration count method. At the 95% confidence interval, the number of individuals ranged from -1,38 ind/ha to 30,20 ind/ha and the number of groups ranged from 0,72 groups/ha to 2,70 groups/ha. Population individual densities ranged from -0,39 ind/ha to 8,83 ind/ha and population group densities ranged from 0,21 groups/ha to 0,79 groups/ha. Structure of long-tailed macaque in the area of Teluk Akar Bergantung city forest on Ketapang, consists of 7,67 individuals of adult male, 9 individuals of adult female, 23,67 individuals of adolescent and 1,33 individual of children. Factors that affect the stability of long-tailed macaque populations include environmental conditions, types of feed, movement, interaction with other animals and the presence of predators.Keywords: Long-tailed macaque, population density, population structure, Teluk Akar Bergantung city forest.